2022
DOI: 10.1146/annurev-micro-040820-010114
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia: A Commensal, Pathogen, and Mutualist of Human and Animal Skin

Abstract: Identified in the late nineteenth century as a single species residing on human skin, Malassezia is now recognized as a diverse genus comprising 18 species inhabiting not only skin but human gut, hospital environments, and even deep-sea sponges. All cultivated Malassezia species are lipid dependent, having lost genes for lipid synthesis and carbohydrate metabolism. The surging interest in Malassezia results from development of tools to improve sampling, culture, identification, and genetic engineering, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 144 publications
(190 reference statements)
0
15
0
Order By: Relevance
“…96 No consistent data exist for differential Malassezia colonization levels on human skin. 13,97 Amplicon and metagenomic sequencing studies generally report relative abundances of individual genera or species. Meanwhile, older culture-based studies suffer from the difficulty of cultivating Malassezia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…96 No consistent data exist for differential Malassezia colonization levels on human skin. 13,97 Amplicon and metagenomic sequencing studies generally report relative abundances of individual genera or species. Meanwhile, older culture-based studies suffer from the difficulty of cultivating Malassezia spp.…”
Section: Discussionmentioning
confidence: 99%
“…10 As such, Staphylococci accumulate in AD lesions and produce toxins that exacerbate epidermal inflammation and barrier disruption. 11,12 Another skin microbe that has been tied to AD is Malassezia , 13 although its causal relationship to the disease is less well established. Malassezia is the most abundant fungus in normal human skin and in many warm-blooded animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This adaptation is linked to their lipid-dependent growth, which is associated with the loss of key genes for fatty acid synthesis (4, 5). At present, the genus Malassezia includes 18 species, with M. restricta , M. arunalokei , M. globosa , M. sympodialis , and M. furfur more commonly observed on human skin regardless of health or disease status (6). While these species are often considered commensals, they can also be mutualistic or pathogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Malassezia is considered the predominant fungus in the human skin. It is a pathobiont involved in various skin diseases, including psoriasis, seborrheic dermatitis, and atopic dermatitis 15 . Studies have indicated a possible role of Malassezia species in chronic diseases occurring at other body sites, such as pancreatic cancer and Alzheimer's disease [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%